1981
DOI: 10.1071/bi9810455
|View full text |Cite
|
Sign up to set email alerts
|

The Foetoplacental Unit and the Initiation of Lactation in the Rat

Abstract: Rats were either Caesarean-sectioned, ovariohysterectomized or ovariectomized on day 19 of gestation anti the role of prolactin and corticosteroids in the initiation of lactation was studied by administering 2~bromo-lX-ergocryptine (CB 154) and prolactin, and by using adrenalectomy and foetectomY. The concentrations of corticosteroids and prolactin in the plasma and the weight and lactose content of the inguinal mammary glands were determined 48 h after Caesarean section, and 24 h after ovariohysterectomy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The increase in milk yield during the first 5 d of lactation was correlated (r 0.76) with the increase in the concentration of lactose in the mammary secretion (Figs 2a and 3). This relationship confirms the conclusion that the increase in the concentration of lactose in milk after birth provides an estimate of the timing of lactogenesis in women as in other species (Hartmann, 1973;Nicholas & Hartmann, 1981). Although the lactose and fat profiles appear similar (Fig.…”
Section: S a I N T Margaret S M I T H A N D P E H A R T M A N Nsupporting
confidence: 83%
See 1 more Smart Citation
“…The increase in milk yield during the first 5 d of lactation was correlated (r 0.76) with the increase in the concentration of lactose in the mammary secretion (Figs 2a and 3). This relationship confirms the conclusion that the increase in the concentration of lactose in milk after birth provides an estimate of the timing of lactogenesis in women as in other species (Hartmann, 1973;Nicholas & Hartmann, 1981). Although the lactose and fat profiles appear similar (Fig.…”
Section: S a I N T Margaret S M I T H A N D P E H A R T M A N Nsupporting
confidence: 83%
“…The abrupt increase in the concentration of lactose in the mammary secretion just before parturition has been shown to be a useful indicator of the increase in the synthetic activity of the mammary glands of rats (Nicholas & Hartmann, 1981) and cows (Hartmann, 1973) during the initiation of lactation. In contrast to other species, the concentration of lactose in the mammary secretion of women remains low during late pregnancy and increases abruptly between 30 and 40 h after parturition .…”
mentioning
confidence: 99%
“…It begins in midpregnancy with the synthesis of milk components (lactogenesis I) and is followed by the onset of copious milk secretion associated with the decrease in progesterone and an increase in prolactin and glucocorticoids around parturition (lactogenesis II) (25,35). Progesterone withdrawal has been identified as the initial trigger of lactogenesis II in rodents (10,25,35,42,46,54). This is supported by the finding that lactogenesis II is impaired as a result of delayed progesterone withdrawal when placental fragments are retained within the uterus of humans and dairy cattle (30).…”
Section: Discussionmentioning
confidence: 99%
“…17 It is known that the onset of milk production is associated with a reduction in maternal progesterone, together with an increase in prolactin and glucocorticoids, around the time of parturition. 20,21 Furthermore, the trigger for secretory activation is characterized by maternal progesterone withdrawal. [20][21][22][23][24] The aim of the current study was to determine whether progesterone, compared to vehicle, administration to rat dams for 2 days following the induction of uteroplacental insufficiency can promote or maintain mammary gland development during late pregnancy and result in an improved lactation and offspring growth after birth.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 Furthermore, the trigger for secretory activation is characterized by maternal progesterone withdrawal. [20][21][22][23][24] The aim of the current study was to determine whether progesterone, compared to vehicle, administration to rat dams for 2 days following the induction of uteroplacental insufficiency can promote or maintain mammary gland development during late pregnancy and result in an improved lactation and offspring growth after birth. Human studies have historically shown that early postpartum progesterone administration increases milk production in uncomplicated pregnancies across the normal birth weight range through yet to be determined mechanisms.…”
Section: Introductionmentioning
confidence: 99%